Microstructural evolution, shielding effectiveness, and the ballistic response of Mg/Al7075/B4C/Pb composite produced by combination of coating and severe plastic deformation (SPD) processes. (December 2022) - Wang, Yinwei; Huang, Pengfei; Liu, Shoufa; Tayyebi, Moslem; Tayebi, Morteza
Abstract: Light-weight metal matrix composites reinforced by Pb and B4 C are of interests in aerospace industry due to high strength to weight ratio and excellent shielding effectiveness. This paper investigates microstructure, shielding effectiveness, tensile properties, and high-velocity impact behavior of Mg/Al/B4 C/Pb composite. In this composite, the B4 C layer was deposited by electrophoretic deposition (EPD) on aluminum layers, then the sandwich with the stacking sequence of Mg/Al/B4 C/Pb was fabricated through accumulative roll bonding (ARB). The optical microscopy (OM) and scanning electron microscopy (SEM) images illustrated that by increasing the cycles, all layers within composite experienced instabilities including necking and fracture. In addition, increasing the number of rolling cycles improved tensile properties, namely Young's modulus, elongation, yield, and ultimate strength. Furthermore, according to the results of the high-velocity impact test, by increasing the rolling cycle, less failure such as cracks and perforation was found on surfaces, indicating the enhanced ballistic resistance of composites. Plus, when composites were subjected to electron radiation, less relative doses of radiation were detected by dosimeter at higher rolling cycles which confirmed the attenuation of transmitted rays and then the enhancement of shielding effectiveness of composites. Highlights: The multilayered composite of Mg/Al/B4C/Pb was fabricated by using electrophoretic deposition (EPD) and accumulative roll bonding (ARB). The tensile properties were improved with an increase in rolling cycles. At higher rolling cycles, the composites were more ballistic resistant against projectile. Better shielding effectiveness was obtained by increasing cycles.